Acidic tumor microenvironment in human melanoma - Böhme, Ines; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2016)
One characteristic of solid tumors such as malignant melanoma is the acidification of the tumor microenvironment. The deregulation of cancer cell metabolism is considered a main cause of extracellular acidosis. Here, cancer cells utilize aerobic glycolysis instead of oxidative phosphorylation even under normoxic conditions, as originally described by Otto Warburg. These metabolic alterations cause enhanced acid production, especially of lactate and carbon dioxide (CO2 ). The extensive production of acidic metabolites and the enhanced acid export to the extracellular space cause a consistent acidification of the tumor microenvironment, thus promoting the formation of an acid-resistant tumor cell population with increased invasive and metastatic potential. As melanoma is one of the deadliest and most metastatic forms of cancer, understanding the effects of this extracellular acidosis on human melanoma cells with distinct metastatic properties is important. The aim of this review was to summarize recent studies of the acidification of the tumor microenvironment, focusing on the specific effects of the acidic milieu on melanoma cells and to give a short overview of therapeutic approaches.
EVALuna2:4736

Alpha-Synuclein and Its Role in Melanocytes - Rachinger, Nicole; Mittag, Nora; Böhme-Schäfer, Ines; Xiang, Wei; Kuphal, Silke; Boßerhoff, Anja Katrin (Cells, 2022)
Pigmentation is an important process in skin physiology and skin diseases and presumably also plays a role in Parkinson’s disease (PD). In PD, alpha-Synuclein (aSyn) has been shown to be involved in the pigmentation of neurons. The presynaptic protein is intensively investigated for its pathological role in PD, but its physiological function remains unknown. We hypothesized that aSyn is both involved in melanocytic differentiation and melanosome trafficking processes. We detected a strong expression of aSyn in human epidermal melanocytes (NHEMs) and observed its regulation in melanocytic differentiation via the microphthalmia-associated transcription factor (MITF), a central regulator of differentiation. Moreover, we investigated its role in pigmentation by performing siRNA experiments but found no effect on the total melanin content. We discovered a localization of aSyn to melanosomes, and further analysis of aSyn knockdown revealed an important role in melanocytic morphology and a reduction in melanosome release. Additionally, we found a reduction of transferred melanosomes in co-culture experiments of melanocytes and keratinocytes but no complete inhibition of melanosome transmission. In summary, this study highlights a novel physiological role of aSyn in melanocytic morphology and its so far unknown function in the pigment secretion in melanocytes.
CRIS-Team Scopus Importer:2022-07-15
Keywords: alpha-Synuclein; melanocytes; melanosomes; pigment transport; pigmentation

Analysis of Glucose Concentration in Melanoma cells under physiological and nutrient-deficient Conditions - Herr, Felix; Schmidt, Sarah; Böhme, Ines; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Extracellular Acidosis leads to the Development of a senescent-like Phenotype and molecular Reprogramming of human Melanoma Cells - Böhme, Ines; Boßerhoff, Anja Katrin (2018)
EVALuna2:203601

Extracellular acidosis leads to the formation of a senescence-like subpopulation in malignant melanoma - Chiheb, Chafia; Böhme-Schäfer, Ines; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Extracellular acidosis triggers a senescence-like phenotype in human melanoma cells - Böhme, Ines; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2019)
Acidosis of the tumor microenvironment is a characteristic of solid tumors such as malignant melanoma. Main causes of the extracellular acidification are metabolic alterations in cancer cells. While numerous studies showed that acidosis promotes tumor invasiveness, metastasis, and neoangiogenesis resulting in malignant progression, contrary data reported that acidosis induces cell apoptosis, inhibits cell proliferation, and mediates cell autophagy. Here, we show that low pH (pH 6.7) induces senescent/quiescent phenotype in melanoma cells after long-time treatment defined by induction of SA-beta-galactosidase, upregulation of p21, G(1)/G(0) cell cycle arrest, and reduction of proliferation. Moreover, we revealed that extracellular acidosis triggers the inhibition of eIF2 alpha and subsequently the activation of ATF4 expression, a key component of the integrated stress response (ISR), indicating an acid-mediated translation reprogramming. Interestingly, we also demonstrated that acidosis represses microphthalmia-associated transcription factor (MITF) and activates the expression of the receptor tyrosine kinase AXL. This MITFlow/AXL(high) phenotype is correlated with drug resistance and therapeutic outcome in melanoma. Our results suggest that acidosis is an important microenvironmental factor triggering phenotypic plasticity and promoting tumor progression.
CRIS-Team WoS Importer:2019-08-20

Importance of the Amino Acid Transporter SNAT1/SLC38A1 in malignant Melanoma - Lörentz, Sandra; Böhme-Schäfer, Ines; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Loss of gene information: Discrepancies between rna sequencing, cdna microarray, and qrt-pcr - Rachinger, Nicole; Fischer, Stefan; Böhme, Ines; Linck-Paulus, Lisa; Kuphal, Silke; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin (International Journal of Molecular Sciences, 2021)
Molecular analyses of normal and diseased cells give insight into changes in gene expression and help in understanding the background of pathophysiological processes. Years after cDNA microarrays were established in research, RNA sequencing (RNA-seq) became a key method of quan-titatively measuring the transcriptome. In this study, we compared the detection of genes by each of the transcriptome analysis methods: cDNA array, quantitative RT-PCR, and RNA-seq. As expected, we found differences in the gene expression profiles of the aforementioned techniques. Here, we present selected genes that exemplarily demonstrate the observed differences and calculations to reveal that a strong RNA secondary structure, as well as sample preparation, can affect RNA-seq. In summary, this study addresses an important issue with a strong impact on gene expression analysis in general. Therefore, we suggest that these findings need to be considered when dealing with data from transcriptome analyses.
CRIS-Team Scopus Importer:2021-09-10
Keywords: CDNA microarray; Free energy of the RNA secondary structure; QRT-PCR; RNA sequencing; Secondary struc-ture; Transcriptome analysis

Membrane Transporters and Channels in Melanoma - Böhme-Schäfer, Ines; Schoenherr, Roland; Eberle, Juergen; Boßerhoff, Anja Katrin (Reviews of Physiology Biochemistry and Pharmacology, 2021)
Recent research has revealed that ion channels and transporters can be important players in tumor development, progression, and therapy resistance in melanoma. For example, members of the ABC family were shown to support cancer stemness-like features in melanoma cells, while several members of the TRP channel family were reported to act as tumor suppressors.
CRIS-Team WoS Importer:2022-03-18
Keywords: Apoptosis; Cell proliferation; Channels; Melanocyte; Melanoma; Metastasis; Mutation; Nevus; Prognosis; Transporters; Tumor development; Tumor progression

Role of Amino Acid Transporter SNAT1/SLC38A1 in Human Melanoma - Böhme-Schäfer, Ines; Lörentz, Sandra; Boßerhoff, Anja Katrin (Cancers, 2022)
The tumor metabolism is an important driver of cancer cell survival and growth, as rapidly dividing tumor cells exhibit a high demand for energetic sources and must adapt to microenviron-mental changes. Therefore, metabolic reprogramming of cancer cells and the associated deregulation of nutrient transporters are a hallmark of cancer cells. Amino acids are essential for cancer cells to synthesize the necessary amount of protein, DNA, and RNA. Although cancer cells can synthesize glutamine de novo, most cancer cells show an increased uptake of glutamine from the tumor microen-vironment. Especially SNAT1/SLC38A1, a member of the sodium neutral amino acid transporter (SNAT) family, plays an essential role during major net import of glutamine. In this study, we revealed a significant upregulation of SNAT1 expression in human melanoma tissue in comparison to healthy epidermis and an increased SNAT1 expression level in human melanoma cell lines when compared to normal human melanocytes (NHEMs). We demonstrated that functional inhibition of SNAT1 with α-(methylamino) isobutyric acid (MeAIB), as well as siRNA-mediated downregulation reduces cancer cell growth, cellular migration, invasion, and leads to induction of senescence in melanoma cells. Consequently, these results demonstrate that the amino acid transporter SNAT1 is essential for cancer growth, and indicates a potential target for cancer chemotherapy.
CRIS-Team Scopus Importer:2022-05-06
Keywords: amino acid transporter; melanoma; tumor metabolism